The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4025/actasciagron.v33i4.11254
|View full text |Cite
|
Sign up to set email alerts
|

Gas exchange of potted Tabebuia aurea plants under hydric stress

Abstract: ABSTRACT.To evaluate the effects of hydric stress on CO 2 and H 2 O exchange, fivemonth-old Tabebuia aurea seedlings cultivated in planting bags were subjected to hydric stress by suppressing irrigation for 21 days. After 14 days without irrigation, the rates of transpiration, stomatal conductance and net photosynthesis in leaves were zero, while the hydric potential of leaves reached -2.4 MPa. After this point, daily irrigation was resumed, and the values of the measured variables recovered to initial levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
8
7
0
1
Order By: Relevance
“…The maximum rate of CO 2 assimilation for control plants in this study was similar to that reported by Oliveira et al (2011) for five-month-old plants of the same species. However, the rates inversely correlated with the duration of flooding, resulting in lower values after 20 and 40 days of stress.…”
Section: Oliveira Akm E Gualtieri Scjsupporting
confidence: 77%
See 1 more Smart Citation
“…The maximum rate of CO 2 assimilation for control plants in this study was similar to that reported by Oliveira et al (2011) for five-month-old plants of the same species. However, the rates inversely correlated with the duration of flooding, resulting in lower values after 20 and 40 days of stress.…”
Section: Oliveira Akm E Gualtieri Scjsupporting
confidence: 77%
“…The leaf water potential of flooded plants was similar to that reported for control plants at 5 months by Oliveira et al (2011). The results obtained from this study indicated that the water potential of T. aurea is not strongly affected by flooding and remains constant.…”
Section: Oliveira Akm E Gualtieri Scjsupporting
confidence: 70%
“…This behavior indicated that other factors influence CO 2 uptake. Further, it suggests the presence of chemical signals in the plants, such as abscisic acid, which control the stomatal opening during drought periods (Hirayama and Shinozaki, 2010;Oliveira et al, 2011). It constitutes a strategy used by the plants to reduce excessive water loss due to transpiration (Albuquerque et al, 2013) and therefore avoiding tissue dehydration, in addition to permitting the maintenance of the integrity of the water transport system and the development of water potential, when the soil is undergoing progressive drought (Magalhães et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Souza et al (2010) studied four species under drought, and did not observe lower conductance rates in all these ones studied, except for Brosimum guianensis. Although Oliveira et al (2011) found similar behavior for five-month-old T. aurea, with declining conductance rates during water stress, the lowest values were found after 14 days of stress. The data obtained for this experiment, with values of 0.0 mol m -2 s -1 after 22 days of stress once more indicate that as individuals become older, their ability to resist to water stress increases.…”
Section: Stomatal Conductancementioning
confidence: 68%
“…This response (leaflets water potential, decrease) was expected, once Mansur and Barbosa (2000) studied Caatinga species, and found that leaflets water potential is reduced by decreasing the availability of water in the soil, causing loss of turgor and stomatal closure. Oliveira et al (2011) studied individuals of T. aurea under stress, and found similar behavior for five-month-old T. aurea, with values between 0.4 and -0.6 MPa for the control plants, and until -2.6 MPa for stressed plants. However, plants with higher growth time (this study) take longer to reach the lowest value of MPa (23 days), while young plants take 14 days, indicating that the longer the growth, the greater the resistance to water stress is.…”
Section: Leaflets Water Potentialmentioning
confidence: 98%